House Prices, Credit Growth, and Excess Volatility: Implications for Monetary and Macroprudential Policy - Paolo Gelain; Kevin J. Lansing; Caterina Mendicino (Norges Bank, 2012)
Progress on the question of whether policymakers should respond directly to financial variables requires a realistic economic model that captures the links between asset prices, credit expansion, and real economic activity. Standard DSGE models with fully-rational expectations have difficulty producing large swings in house prices and household debt that resemble the patterns observed in many developed countries over the past decade. We introduce excess volatility into an otherwise standard DSGE model by allowing a fraction of households to depart from fully-rational expectations. Specifically, we show that the introduction of simple moving-average forecast rules for a subset of households can significantly magnify the volatility and persistence of house prices and household debt relative to otherwise similar model with fully-rational expectations. We evaluate various policy actions that might be used to dampen the resulting excess volatility, including a direct response to house price growth or credit growth in the central bank's interest rate rule, the imposition of more restrictive loan-to-value ratios, and the use of a modified collateral constraint that takes into account the borrower's loan-to-income ratio. Of these, we find that a loan-to-income constraint is the most effective tool for dampening overall excess volatility in the model economy. We find that while an interest-rate response to house price growth or credit growth can stabilize some economic variables, it can significantly magnify the volatility of others, particularly inflation.
hdl:11250/2496831
Keywords: E32; E44; G12; O40; 330; asset pricing; excess volatility; credit cycles; housing bubbles; monetary policy; macroprudential policy